Efektivitas blended learning terintegrasi model pemetaan Bloom–Rederker–Guerra (B–R–G) memberdayakan self-regulated learning peserta didik - Arsad Bahri; Irma Suryani Idris; Nikhrawati Zaid (Seminar Nasional LP2M UNM, 2019)
The 21st century learning paradigm requires teachers to be able to integrate using technology, information, and communication (ICT) in learning. Technological, Pedagogical, Content, and Knowledge (TPACK) is a framework in designing new learning models by integrating technology in teaching. This research is a quasi-experimental study with the research design of The One Group Pretest-posttest which aims to test the effectiveness of an integrated blended learning environment in the Bloom-Redekker_Guerra mapping model in empowering self-regulated learning of students. The study was conducted in the XI MIA 1 class of Gowa 10 Senior High Schools totaling 36 students in the odd semester of the academic year 208/2019. Self-regulated lerning (metacognitive skills) of students is measured using an essay test that is integrated with the achievement test. Data were analyzed using descriptive techniques. The results showed that the integrated blended learning environment of the Bloom-Rederker-Guerra (B – R – G) mapping model was effective in empowering the self-regulate learning of students. Therefore, the integration of ICT in learning is seen as important to do so that the learning independence of students can be trained.